Sustainable design elements for urban street micro-architecture in Malaysia - M. Tazilan, Azimin Samsul; Salleh, Hood; Komoo, Ibrahim; Ismail, Abdul Halim (Faculty of Design & Architecture, Universiti Putra Malaysia, 2008)
Streets microarchitecture constructs are compact structures such as stalls, kiosks, phone booths, and toilets that one finds as one walks on the streets, alleys, walkways, pedestrian malls and such. Because of its smallness, they are usually seen to be unimportant in the development of townships and cities. In this paper a series of street investigation of human behavior within the retail built environment projected a unique results on how formal and informal street space is cultured. As Jacob (1993) stated a great street should have characters, therefore this event can bond a specific street identity within and would become a tourism product besides the daily retail activity. Microarchitecture, however, actually gives the first real impression of a town, city or country to visitors to a particular place or locale. Its impact is immediate and opinions are formed of the place and its people quite instantaneously. A lot of street micro-architecture are public amenities such as toilets and squares. Base on current phenomenology research studied, it gives a better justification on sustainable elements approach on street microahitecture in Malaysia. Thus, in this research and practise base paper, it is imperative to study and understand its functions, aesthetics and design elements so that a sustainable architectural plan and street identity can be developed for the comfort of locals and visitors alike.